1971
DOI: 10.1021/ja00752a016
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of isotopic oxygen exchange and reduction of ferrate(VI) ion (FeO42-)

Abstract: k = 1.62 X 10-2 sec-1 at 25", log A = 9.51 =t 0.79, and E, = 15.4 & 1.0 kcal/mol. 6+ Fe is Fe02-and all oxygens are kinetically equivalent. celerated by dilute acid. HzO, HzOZ, and SO?-, and the results are compared with other strong oxidizing agents. and S03*-are quantitative and show simple stoichiometry. in S032-, but oxygen transfer from Fe042-to the product (02 or S042-) occurs only in the latter case.In basic media the rate of 1 8 0 exchange between Fe042-and water follows the law R = k[FeO4*-1, whereIn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
2
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(117 citation statements)
references
References 3 publications
6
106
2
3
Order By: Relevance
“…The tetrahedral structure was also confirmed by isotopic exchange study as performed in aqueous solutions [19]. The reliable simulated powder XRD patterns (ICSD file 2876 and 32756, [20]) and an experimental one (PDF file No.…”
Section: Mössbauer Spectroscopic Analysismentioning
confidence: 68%
See 4 more Smart Citations
“…The tetrahedral structure was also confirmed by isotopic exchange study as performed in aqueous solutions [19]. The reliable simulated powder XRD patterns (ICSD file 2876 and 32756, [20]) and an experimental one (PDF file No.…”
Section: Mössbauer Spectroscopic Analysismentioning
confidence: 68%
“…The oxygen produced in this reaction showed the same isotopic composition as in the H 2 O 2 , which suggested that the O-O bond was retained in the oxidation of H 2 O 2 by ferrate(VI) [19].…”
Section: Application Of Fe(vi) For Inorganic Pollutantsmentioning
confidence: 69%
See 3 more Smart Citations